Comparison of Rituximab Originator With CT-P10 Biosimilar in Patients With Primary Sjögren's Syndrome: A Retrospective Analysis in a Real-Life Setting - Pavlych, Viktoriya; Di Muzio, Claudia; Alunno, Alessia; Carubbi, Francesco (Frontiers in Medicine, 2020)
Introduction: Over the last 2 decades rituximab (RTX) has been widely used, albeit off-label, in primary Sjögren’s syndrome (pSS). Several studies reported that B-lymphocyte depletion with RTX is effective to treat some aspects within the disease spectrum, by reducing disease activity and affecting the inflammation and lymphoid organization that occurs in target tissues. Notwithstanding, randomized controlled trials failed to confirm such evidence. With the recent release of several RTX biosimilars on the market, their efficacy and safety compared to the originator must be ascertained across different indications. This study aimed at comparing the efficacy and safety of RTX originator and CT-P10 RTX biosimilar in pSS patients in a real-life setting. Methods: Clinical and laboratory records of pSS patients referring to a tertiary rheumatology clinic were retrospectively evaluated. Patients having received at least 2 courses of either RTX originator or CT-P10 with complete data at baseline and after 12, 24, 36, and 48 weeks of treatment were enrolled. Disease activity was assessed with the EULAR SS disease activity index (ESSDAI) and its clinical version without the biological domain (clinESSDAI). Patient-reported symptoms were assessed with the EULAR SS Patient Reported Index (ESSPRI). Adverse events (AEs) occurring during the study period were also recorded. Results: Nine patients that received RTX originator and 8 patients that received CT-P10 were enrolled. Baseline clinical and serological features, including ESSDAI and ESSPRI were similar in the 2 treatment groups. The efficient depletion of circulating CD19+ B-lymphocytes was achieved in both treatment arms. Both RTX originator and CT-P10 significantly reduced ESSDAI and clinESSDAI by week 24 and no difference between the groups was observed at any time point. Conversely, changes of ESSPRI overtime did not differ between the two treatment arms and were not statistically significant compared to corresponding baseline values. With regard to safety, at 48 weeks of follow-up only 4 mild AEs (2 in the RTX originator and 2 in the CT-P10 group) were observed. Conclusion: Our study provides the first evidence that at 48 weeks of follow-up, RTX originator and CT-P10 display similar efficacy and safety profiles in pSS.